Venerating the cross - Mumbai Archive Project Team (Jio Institute, 2024)
The faithful are invited to approach and venerate the cross, often by kissing it, touching it, or bowing before it. This act of reverence enables worshippers to establish a personal connection with the Passion of Christ.